Transformation through learning: Education about, for, and as sustainability - Gajparia, Jaya; Strachan, Glenn; Leverton, Kris (Frontiers in Sustainability, 2022)
The United Nations foregrounds education as a means to achieving the Sustainable Development Goals (https://sdgs.un.org/goals). In this conceptual paper, we argue education must offer learning that is transformative to better prepare learners to respond to the current global challenges. We argue that the dominant educational approaches fall short of realizing learners' potential for transformation toward sustainability. Focusing on the region of Southeast Asia we draw on educator experiences working with and at the Green School (Indonesia) and United World College (Singapore) to map some of their educational successes and identify some of the key processes and conditions that have contributed to those successes. The potential that exists in the context of independent international schools maybe a relevant factor in their success. We see the lessons that can be learned from these examples as useful in other school contexts. We draw on three sequential pedagogical development phases of learning in engaging with sustainability: namely, Learning about Sustainability, Learning for Sustainability (LfS), and Learning as Sustainability. We argue that the third transformative learning phase, Learning as Sustainability (which also incorporates processes of learning about and for sustainability) offers the best fertile ground for engaging learners as active social change agents within and outside of the learning environment. We see these learning phases as all interconnected, dynamic, and fluid rather than a formulaic progression. This paper contributes to advancing schools toward a perspective on education that reflects an ecological approach toward sustainability and support educators to better integrate education as sustainability in their learning activities. It is worth mentioning that changes in the school that reflect an ecological approach does not guarantee that the experience of the learner will result in transformative Learning as Sustainability. Instead, it is our contention that attaining a clear understanding of these learning processes empowers educators to facilitate an environment by identifying and incorporating the necessary conditions required to inspire deep ecological transformation, thus increasing the potential to arrive at Learning as Sustainability.